Influence of Flax Fibre Hybridization on Mechanical Behaviour of Sisal Fibre-Polypropylene Composites Prepared with an Injection Moulding Machine - J. Allen Jeffrey; A. Sivakumar; R. Naveen Kumar; A. Anbazhagan; G. Manojkumar; Sami Al Obaid; Saleh Alfarraj; S. Sivakumar; S. Rajkumar (Advances in Materials Science and Engineering)
Due to their low weight, high specific strength, and low environmental impact, sisal fibre-polypropylene composites have gained popularity. However, the material has a low modulus and poor moisture resistance, among other shortcomings. This study investigated how flax fibre hybridization affects the physical parameters of sisal fibre-polypropylene composites. We used maleic anhydride-grafted polypropylene to improve compatibility between fibres and polypropylene. Adding flax fibres to polypropylene-silica composites resulted in increased tensile strength, flexibility, and impact strength, according to researchers. Water resistance was further improved by adding flax fibres. Tensile strength values of polypropylene-sisal fibre composites filled with 0, 5, 10, 15, and 20 wt% of flax fibres were 29.46, 30.56, 31.57, 33.12, and 34.64 MPa, respectively.